Regional Spatial Approach to Differences in Rural Economic Development: Insights from Serbia - Žana Jurjević; Stanislav Zekić; Danilo Đokić; Bojan Matkovski (Land, 2021)
Rural regions with a larger share of the primary sector in the overall economy are limited in their ability to achieve a sufficient level of competitiveness. In countries such as Serbia, where rural areas play an important role, addressing the problems affecting these areas is important for overall development. The purpose of this study is to determine the socioeconomic performance of the rural regions of Serbia and the EU in order to indicate the position of Serbia’s rural areas in the process of European integration. NUTS 3 (NUTS 2 for Germany) was used for analysis, and from this an Index of Socioeconomic Performance was created. This Index was created using Factor Analysis. The results point to Serbia lagging behind other EU regions in terms of development, with most of Serbia’s rural regions receiving the lowest ratings. These results are cause for alarm and indicate a need to create strategies that will direct resources towards key issues in these areas, whose potential would be adequately used through the implementation of rural policy measures, with the aim of overall socioeconomic development.